Organizational Structure and its Impact on Performance - Acharya Kaphle, Sushmita (Curriculum Development Journal, 2023)
The purpose of this study is to seek the impact of organizational structure on performance of local government. The establishment and functioning of appropriate organizational structures and processes at the grassroots levels is crucial for addressing the local needs and aspirations. This study analyses organizational structure from three different perspectives such as (i) Centralization, ii. Formalization, and iii. Specialization and has an impact on organizational performance. Following a pragmatic approach, this study applied a mixed methods research design incorporating in-depth interviews with local government officials. The findings prevail the facts that there exists a lesser extent of differentiation in municipality, and organization structure is found to have a low pace of support to the organizational performance and employees are demanding for a more supportive environment and role clarity. The study shows that even today the municipality office has not been able to promote the downward accountability in the organizations as expected. A local governance realization in improving performance highly depends on the skills and motivation of its workforce and team spirit. Employee involvement in decision making creates bonds for commitment and performance. In the overall picture, organization structure is somehow urging towards organizational performance. So far, the majority of respondents are positive towards the role played by municipalities for local development.